Identification of the estrogen receptor GPER in neoplastic and non-neoplastic human testes - Maggiolini Marcello; Giordano Francesca; Romeo Francesco; Rago Vittoria; Carpino Amalia (BMC, 2011)
Abstract Background Estrogen signaling is mediated by estrogen receptor beta isoforms in normal and neoplastic human testes. Recently, a G-protein-coupled-receptor (GPER) has been suggested as being involved in rapid responses to estrogens in different normal and tumor cells. Methods This study investigated the GPER expression in paraffin-embedded samples from non neoplastic and neoplastic human testes (sex-cord stromal and germ cell tumors) by immunohistochemical and Western Blot analyses. Results In control testes, a positive GPER immunoreactivity was detected in Leydig and in Sertoli cells while all germ cells were immunonegative. Furthermore, neoplastic cells of the Sertoli cell tumor, Leydig cell tumor, seminoma and embryonal carcinoma samples were all immunopositive. The immunoblots of testis extracts confirmed the results. Conclusions These findings suggest that GPER could mediate estrogen signaling in both normal and transformed somatic cells of human testis, but they reveal a differential expression of the novel estrogen receptor in non neoplastic and neoplastic germ cells.